Audit Manajemen Dalam Penilaian Efektivitas Fungsi Sumber Daya Manusia Pada PT. Hotel Griyadi Montana Kota Malang - Hendrik, Lukman; Achmad, Komarudin (Jurnal Ilmiah Mahasiswa FEB, 2012)
Management audit that applied to human resource function at PT. HotelGriyadi Montana Malang aim to know effectiveness execution of human resourcefunction that may be there are some weakness. The type of this research isqualitative descriptive research. Data collecting of this research are by interview,literate study, informan and observation. Effectiveness assessment of humanresource function analysed and evaluated by comparing criteria, causes, andeffect. And the result of this research analysis show management of humanresource function at PT. Hotel Griyadi Montana Malang in general is not effectiveyet, and still there are some weakness of management in which need to becorrected and repaired. In attainment of human resource function target do notfounded a big resistance. But, PT. Hotel Griyadi Montana Malang has continuedto improve performance and evaluation human resource function so thatperformance in the future get better than this time.Keyword : Management Audit, effectiveness, human resource function